PENINGKATAN KETERAMPILAN MENGIDENTIFIKASI UNSUR INTRINSIK CERPEN MENGGUNAKAN MODEL KOOPERATIF TIPEPAIR CHECK - Garagasi, Albedhmake Vandaras; Priyadi, A. Totok; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractA general problem in this research is how the improvement of identifying the intrinsic elements skills of short story using the cooperative model type of Pair Check at the students of XI IPS SMA WidyaPratama, Kecamatan Sungai Raya, KabupatenKubu Raya?